Preparation and application of MOF-5 thermal crosslinking modified polyimide film
By introducing MOF-5 into the polyimide film and performing heat cross-linking treatment, the problem of low helium flux and selectivity in the existing gas separation membrane technology is solved, and high-efficiency helium separation and good anti-plasticization performance are achieved.
Patent Information
- Application Number
- CN202510172871.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing gas separation membrane technology has problems such as low flux and selectivity and difficulty in preparation during the helium extraction process, which is difficult to meet the needs of efficient helium separation.
The MOF-5 heat crosslinked modified polyimide film is used. By introducing MOF-5 into the polyimide film and performing heat crosslinking treatment, the hydrogen flux and selectivity of the film are enhanced and the anti-plasticization performance is enhanced.
It significantly improves the flux and selectivity of helium, improves the anti-plasticization performance of the film, makes the helium separation efficiency stable, and can effectively separate helium from other gases.
Smart Images

Figure CN119869250A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas separation, and more specifically, to the preparation and application of a MOF-5 thermally cross-linked modified polyimide film. Background Art
[0002] Helium is a non-renewable resource with unique properties such as low boiling point, good thermal conductivity, good permeability, stable properties, and no solidification at absolute zero. Therefore, helium is widely used in aerospace, military industry, submarines, cutting-edge scientific research, high-end manufacturing, medical treatment and other fields, and is an indispensable strategic material for the development of national defense military industry and high-tech industry.
[0003] With the continuous improvement of science and technology and the increase in scientific research activities, the demand for helium is also increasing, driving the development of the market. Natural gas is the main source of raw materials for the preparation of helium, but the main component of natural gas is methane, and other types of impurity gases also exist in natural gas, which also increases the difficulty of helium extraction. The use of traditional preparation methods has the disadvantages of high energy consumption and low purity of the prepared gas. The membrane separation technology that has emerged in recent years can extract helium simply, quickly and efficiently. This method uses pressure to make the mixed gas pass through the separation membrane to obtain high-purity separation gas. It has many advantages such as low cost, high energy efficiency, small footprint, simple equipment, easy regulation and green and pollution-free, and has great potential in gas separation applications. However, in the process of practical application and research in recent years, gas separation membrane technology has also exposed many problems, such as difficulty in controlling uniformity, low selectivity, and difficulty in preparation.
[0004] Patent document CN116571099A discloses a carbon molecular sieve membrane and its preparation method and application. The preparation method improves the pore structure and distribution of the carbon molecular sieve membrane by adding rare earth salts for rare earth coordination modification and carbonization, but the helium / methane selectivity is only at the level of 28-168, and the helium flux and selectivity are both low.
[0005] Patent document CN115945079A discloses a preparation method and application of a fluorine-containing cross-linkable polyimide-based carbon molecular sieve membrane. The preparation method introduces fluorine elements into polyimide monomer compounds to effectively modify the internal defects of the polyimide film. However, the selectivity of this film for helium / methane is only 53 and the flux cannot be improved. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing and applying a MOF-5 thermally cross-linked modified polyimide film, which has stable gas separation efficiency, can effectively improve the flux and selectivity of helium, and has good anti-plasticization performance.
[0007] A method for preparing a MOF-5 thermally cross-linked modified polyimide film, characterized in that it comprises the following steps:
[0008] S1: Preparation of α-Al2O3 support, grinding α-Al2O3 powder and pressing it into sheets, drying, high-temperature firing, grinding, cleaning and drying to obtain α-Al2O3 support, which is dried and stored for later use;
[0009] S2: Synthesis of MOF-5, Zn(NO3)·6H2O and 1,4-phthalic acid were dissolved in DMF solvent, reacted in an oil bath, and the product obtained by the reaction was filtered, rinsed and dried to obtain MOF-5;
[0010] S3: Preparation of casting solution: dissolving polyimide in a solvent, then adding MOF-5, heating, stirring, and vacuum degassing to obtain a casting solution;
[0011] S4: Preparation of MOF-5 thermally cross-linked modified polyimide film, spin-spraying the casting liquid onto an α-Al2O3 support, and obtaining a spin-sprayed film after natural drying, and immersing the spin-sprayed film in a solvent, vacuum drying, and calcining the dried spin-sprayed film under an inert gas atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film, and storing the obtained MOF-5 thermally cross-linked modified polyimide film under an inert gas atmosphere.
[0012] Further, step S1: preparation of α-Al2O3 support, specifically comprising the following steps:
[0013] S1.1: Pour α-Al2O3 powder into a mortar, add deionized water and grind vigorously until the powder is uniform;
[0014] S1.2: Pour the ground α-Al2O3 powder into a film-making mold and press it into a sheet using a film press to obtain a film sheet;
[0015] S1.3: Place the membrane in a humidity chamber at a temperature of 40-55°C and a humidity of 60-65% to allow the membrane to lose water slowly and not easily break;
[0016] S1.4: placing the dried membrane into a high temperature furnace and sintering it at 1200-1300°C to form an α-Al2O3 carrier to serve as a support for the membrane;
[0017] S1.5: Place the fired α-Al2O3 slide on a polishing machine for polishing, then rinse with deionized water, and then soak with alcohol to remove oil stains and dirt on the surface of the α-Al2O3 slide;
[0018] S1.6: Finally, the soaked α-Al2O3 substrate is placed in an oven for drying to obtain an α-Al2O3 support body, which is then dried and stored for later use.
[0019] Further, step S2: synthesis of MOF-5 specifically includes the following steps:
[0020] S2.1: Add the DMF solvent that has been previously dehydrated by a 4A molecular sieve into a round-bottom flask, introduce nitrogen into the round-bottom flask to fully discharge the oxygen dissolved in the DMF solvent, and obtain a pretreated DMF solvent;
[0021] S2.2: Then, Zn(NO3)·6H2O and 1,4-phthalic acid in a molar ratio of 1:4 are added to the round-bottom flask and gently shaken until they are evenly dissolved. After Zn(NO3)·6H2O and 1,4-phthalic acid are completely dissolved in the pretreated DMF solvent, the liquid in the round-bottom flask is transferred to a glass container, the glass container is sealed with a cover and reacted in a constant temperature oil bath. After the reaction is completed, the glass container is taken out from the oil bath and placed in the air to cool naturally to room temperature;
[0022] S2.3: The product obtained by the reaction is filtered out and repeatedly washed with DMF solution to dissolve and remove unreacted zinc ions and 1,4-phthalic acid;
[0023] S2.4: Finally, the rinsed sample is immersed in chloroform and placed in a vacuum oven to dry to obtain MOF-5.
[0024] Further, step S3: preparing the casting solution, specifically comprises the following steps:
[0025] Dissolve polyimide in a solvent, stir at 40-80°C for 12-36 hours, then add MOF-5 and stir at 60-80°C for 12-36 hours, then vacuum degassing for 6-12 hours to obtain a casting solution.
[0026] Furthermore, MOF-5 accounts for 3-10% of the mass of polyimide, and polyimide accounts for 20-30% of the total mass of the casting solution.
[0027] Further, step S4: preparation of MOF-5 thermally cross-linked modified polyimide film, specifically comprising the following steps:
[0028] The casting liquid is poured into the liquid storage tank of the rotary spraying machine, and the casting liquid is evenly rotary sprayed onto the α-Al2O3 support. After natural drying, a rotary sprayed film is obtained. The rotary sprayed film is soaked in a solvent for 3-6 days, and then vacuum dried at 40-80°C for 8-12 hours. Subsequently, the dried rotary sprayed film is placed in a tubular furnace and calcined at 200-300°C for 2-4 hours in an inert gas atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film. The obtained MOF-5 thermally cross-linked modified polyimide film is stored in an inert gas atmosphere.
[0029] Furthermore, the solvent is any one of nitrogen-methylpyrrolidone and N,N-dimethylformamide.
[0030] Furthermore, the inert gas in step S4 is nitrogen.
[0031] A MOF-5 thermally cross-linked modified polyimide film is prepared by a method for preparing a MOF-5 thermally cross-linked modified polyimide film.
[0032] Application of MOF-5 thermally cross-linked modified polyimide film in helium separation.
[0033] The present invention has the following advantages:
[0034] 1. In the present invention, a MOF-5 thermally cross-linked modified polyimide film is prepared. The introduction of MOF-5 can significantly improve the selectivity and permeability of the polyimide film to helium. The structure of MOF-5 contains a large number of carboxyl functional groups that can form intermolecular hydrogen bonds with polyimide, thereby effectively increasing the mechanical stability and skeleton stability of MOF-5 in polyimide and modifying the structural defects in polyimide. At the same time, MOF-5 has the advantages of stable structure, large specific surface area and large porosity. The MOF-5 thermally cross-linked modified polyimide film is prepared by thermal cross-linking, which can effectively improve the flux and selectivity of helium and the plasticization resistance of the polyimide film.
[0035] 2. In the present invention, the preparation method of the MOF-5 thermally cross-linked modified polyimide film is simple and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a graph showing the plasticization resistance of the MOF-5 thermally cross-linked modified polyimide film prepared in Example 4 of the present invention;
[0037] Figure 2 This is a graph showing the anti-plasticization performance of the polyimide film prepared in Comparative Example 1 of the present invention;
[0038] Figure 3 This is a graph showing the anti-plasticization performance of the MOF-5 modified polyimide film prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] A method for preparing a MOF-5 thermally cross-linked modified polyimide film, specifically comprising the following steps:
[0042] S1: Preparation of α-Al2O3 support,
[0043] S1.1: Pour α-Al2O3 powder into a mortar, add deionized water and grind vigorously until the powder is uniform;
[0044] S1.2: Pour the ground α-Al2O3 powder into a film-making mold and press it into a sheet using a film press to obtain a film sheet;
[0045] S1.3: Place the membrane in a humidity chamber at 40°C and 60% humidity to allow the membrane to slowly lose water and not easily break;
[0046] S1.4: placing the dried membrane into a high temperature furnace and sintering at 1200°C to form an α-Al2O3 carrier with a macroporous structure to serve as a support for the membrane;
[0047] S1.5: Place the fired α-Al2O3 slide on a polishing machine for polishing, then rinse with deionized water, and then soak with alcohol to remove oil stains and dirt on the surface of the α-Al2O3 slide;
[0048] S1.6: Finally, the soaked α-Al2O3 substrate is placed in an oven for drying to obtain an α-Al2O3 support, and the α-Al2O3 support is placed in a desiccator for storage;
[0049] S2: Synthesis of MOF-5,
[0050] S2.1: Add the DMF solvent that has been previously dehydrated by a 4A molecular sieve into a round-bottom flask, introduce nitrogen into the round-bottom flask to fully discharge the oxygen dissolved in the DMF solvent, and obtain a pretreated DMF solvent;
[0051] S2.2: Then, Zn(NO3)·6H2O and 1,4-phthalic acid in a molar ratio of 1:4 are added to the round-bottom flask and gently shaken until they are evenly dissolved. After Zn(NO3)·6H2O and 1,4-phthalic acid are completely dissolved in the pretreated DMF solvent, the liquid in the round-bottom flask is transferred to a glass container, the glass container is sealed with a cover and reacted in a constant temperature oil bath. After the reaction is completed, the glass container is taken out from the oil bath and placed in the air to cool naturally to room temperature;
[0052] S2.3: The product obtained by the reaction is filtered out and repeatedly washed with DMF solution to dissolve and remove unreacted zinc ions and 1,4-phthalic acid;
[0053] S2.4: Finally, the rinsed sample is immersed in chloroform and dried in a vacuum oven to obtain MOF-5;
[0054] S3: Preparation of casting solution,
[0055] The polyimide P84 powder was dissolved in N, N-dimethylformamide, stirred at 40°C for 12 hours, then MOF-5 was added and stirred at 60°C for 12 hours, and then vacuum degassing was performed for 6 hours to obtain a casting solution, wherein MOF-5 accounted for 3% of the mass of the polyimide P84 powder, and the polyimide P84 powder accounted for 20% of the total mass of the casting solution;
[0056] S4: Preparation of MOF-5 thermally cross-linked modified polyimide film,
[0057] The casting liquid is poured into the liquid storage tank of the rotary spraying machine, and the casting liquid is evenly rotary sprayed onto the α-Al2O3 support. After natural drying, a rotary sprayed film is obtained. The rotary sprayed film is soaked in N, N-dimethylformamide for 3 days, and then vacuum dried at 40°C for 8 hours. Subsequently, the dried rotary sprayed film is placed in a tubular furnace and calcined at 200°C for 2 hours in a nitrogen atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film. The obtained MOF-5 thermally cross-linked modified polyimide film is stored in a nitrogen atmosphere.
[0058] Example 2
[0059] A method for preparing a MOF-5 thermally cross-linked modified polyimide film, specifically comprising the following steps:
[0060] S1: Preparation of α-Al2O3 support,
[0061] S1.1: Pour α-Al2O3 powder into a mortar, add deionized water and grind vigorously until the powder is uniform;
[0062] S1.2: Pour the ground α-Al2O3 powder into a film-making mold and press it into a sheet using a film press to obtain a film sheet;
[0063] S1.3: Place the membrane in a humidity chamber at 45°C and 61% humidity to allow the membrane to lose water slowly and not easily break;
[0064] S1.4: Place the dried membrane into a high temperature furnace and sinter at 1225°C to form an α-Al2O3 carrier with a macroporous structure to serve as a support for the membrane;
[0065] S1.5: Place the fired α-Al2O3 slide on a polishing machine for polishing, then rinse with deionized water, and then soak with alcohol to remove oil stains and dirt on the surface of the α-Al2O3 slide;
[0066] S1.6: Finally, the soaked α-Al2O3 substrate is placed in an oven for drying to obtain an α-Al2O3 support, and the α-Al2O3 support is placed in a desiccator for storage;
[0067] S2: Synthesis of MOF-5,
[0068] S2.1: Add the DMF solvent that has been previously dehydrated by a 4A molecular sieve into a round-bottom flask, introduce nitrogen into the round-bottom flask to fully discharge the oxygen dissolved in the DMF solvent, and obtain a pretreated DMF solvent;
[0069] S2.2: Then, Zn(NO3)·6H2O and 1,4-phthalic acid in a molar ratio of 1:4 are added to the round-bottom flask and gently shaken until they are evenly dissolved. After Zn(NO3)·6H2O and 1,4-phthalic acid are completely dissolved in the pretreated DMF solvent, the liquid in the round-bottom flask is transferred to a glass container, the glass container is sealed with a cover and reacted in a constant temperature oil bath. After the reaction is completed, the glass container is taken out from the oil bath and placed in the air to cool naturally to room temperature;
[0070] S2.3: The product obtained by the reaction is filtered out and repeatedly washed with DMF solution to dissolve and remove unreacted zinc ions and 1,4-phthalic acid;
[0071] S2.4: Finally, the rinsed sample is immersed in chloroform and dried in a vacuum oven to obtain MOF-5;
[0072] S3: Preparation of casting solution,
[0073] The polyimide P84 powder was dissolved in N, N-dimethylformamide, stirred at 50°C for 24 hours, then MOF-5 was added and stirred at 60°C for 24 hours, and then vacuum degassing was performed for 8 hours to obtain a casting solution, wherein MOF-5 accounted for 5% of the mass of the polyimide P84 powder, and the polyimide P84 powder accounted for 23% of the total mass of the casting solution;
[0074] S4: Preparation of MOF-5 thermally cross-linked modified polyimide film,
[0075] The casting liquid is poured into the liquid storage tank of the rotary spraying machine, and the casting liquid is evenly rotary sprayed onto the α-Al2O3 support. After natural drying, a rotary sprayed film is obtained. The rotary sprayed film is soaked in N, N-dimethylformamide for 4 days, and then vacuum dried at 50°C for 9 hours. The dried rotary sprayed film is then placed in a tubular furnace and calcined at 225°C for 2 hours under a nitrogen atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film. The obtained MOF-5 thermally cross-linked modified polyimide film is stored in a nitrogen atmosphere.
[0076] Example 3
[0077] A method for preparing a MOF-5 thermally cross-linked modified polyimide film, specifically comprising the following steps:
[0078] S1: Preparation of α-Al2O3 support,
[0079] S1.1: Pour α-Al2O3 powder into a mortar, add deionized water and grind vigorously until the powder is uniform;
[0080] S1.2: Pour the ground α-Al2O3 powder into a film-making mold and press it into a sheet using a film press to obtain a film sheet;
[0081] S1.3: Place the membrane in a humidity chamber at 50°C and 63% humidity to allow the membrane to lose water slowly and not easily break;
[0082] S1.4: placing the dried membrane into a high temperature furnace and sintering at 1250°C to form an α-Al2O3 carrier with a macroporous structure to serve as a support for the membrane;
[0083] S1.5: Place the fired α-Al2O3 slide on a polishing machine for polishing, then rinse with deionized water, and then soak with alcohol to remove oil stains and dirt on the surface of the α-Al2O3 slide;
[0084] S1.6: Finally, the soaked α-Al2O3 substrate is placed in an oven for drying to obtain an α-Al2O3 support, and the α-Al2O3 support is placed in a desiccator for storage;
[0085] S2: Synthesis of MOF-5,
[0086] S2.1: Add the DMF solvent that has been previously dehydrated by a 4A molecular sieve into a round-bottom flask, introduce nitrogen into the round-bottom flask to fully discharge the oxygen dissolved in the DMF solvent, and obtain a pretreated DMF solvent;
[0087] S2.2: Then, Zn(NO3)·6H2O and 1,4-phthalic acid in a molar ratio of 1:4 are added to the round-bottom flask and gently shaken until they are evenly dissolved. After Zn(NO3)·6H2O and 1,4-phthalic acid are completely dissolved in the pretreated DMF solvent, the liquid in the round-bottom flask is transferred to a glass container, the glass container is sealed with a cover and reacted in a constant temperature oil bath. After the reaction is completed, the glass container is taken out from the oil bath and placed in the air to cool naturally to room temperature;
[0088] S2.3: The product obtained by the reaction is filtered out and repeatedly washed with DMF solution to dissolve and remove unreacted zinc ions and 1,4-phthalic acid;
[0089] S2.4: Finally, the rinsed sample is immersed in chloroform and dried in a vacuum oven to obtain MOF-5;
[0090] S3: Preparation of casting solution,
[0091] The polyimide P84 powder was dissolved in N, N-dimethylformamide, stirred at 60°C for 24 hours, then MOF-5 was added and stirred at 70°C for 24 hours, and then vacuum degassing was performed for 10 hours to obtain a casting solution, wherein MOF-5 accounted for 7% of the mass of the polyimide P84 powder, and the polyimide P84 powder accounted for 26% of the total mass of the casting solution;
[0092] S4: Preparation of MOF-5 thermally cross-linked modified polyimide film,
[0093] The casting liquid is poured into the liquid storage tank of the rotary spraying machine, and the casting liquid is evenly rotary sprayed onto the α-Al2O3 support. After natural drying, a rotary sprayed film is obtained. The rotary sprayed film is soaked in N, N-dimethylformamide for 5 days, and then vacuum dried at 60°C for 10 hours. Subsequently, the dried rotary sprayed film is placed in a tubular furnace and calcined at 250°C for 3 hours in a nitrogen atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film. The obtained MOF-5 thermally cross-linked modified polyimide film is stored in a nitrogen atmosphere.
[0094] Example 4
[0095] A method for preparing a MOF-5 thermally cross-linked modified polyimide film, specifically comprising the following steps:
[0096] S1: Preparation of α-Al2O3 support,
[0097] S1.1: Pour α-Al2O3 powder into a mortar, add deionized water and grind vigorously until the powder is uniform;
[0098] S1.2: Pour the ground α-Al2O3 powder into a film-making mold and press it into a sheet using a film press to obtain a film sheet;
[0099] S1.3: Place the membrane in a humidity chamber at 55°C and 65% humidity to allow the membrane to slowly lose water and not easily break;
[0100] S1.4: placing the dried membrane into a high temperature furnace and sintering at 1300°C to form an α-Al2O3 carrier with a macroporous structure to serve as a support for the membrane;
[0101] S1.5: Place the fired α-Al2O3 slide on a polishing machine for polishing, then rinse with deionized water, and then soak with alcohol to remove oil stains and dirt on the surface of the α-Al2O3 slide;
[0102] S1.6: Finally, the soaked α-Al2O3 substrate is placed in an oven for drying to obtain an α-Al2O3 support, and the α-Al2O3 support is placed in a desiccator for storage;
[0103] S2: Synthesis of MOF-5,
[0104] S2.1: Add the DMF solvent that has been previously dehydrated by a 4A molecular sieve into a round-bottom flask, introduce nitrogen into the round-bottom flask to fully discharge the oxygen dissolved in the DMF solvent, and obtain a pretreated DMF solvent;
[0105] S2.2: Then, Zn(NO3)·6H2O and 1,4-phthalic acid in a molar ratio of 1:4 are added to the round-bottom flask and gently shaken until they are evenly dissolved. After Zn(NO3)·6H2O and 1,4-phthalic acid are completely dissolved in the pretreated DMF solvent, the liquid in the round-bottom flask is transferred to a glass container, the glass container is sealed with a cover and reacted in a constant temperature oil bath. After the reaction is completed, the glass container is taken out from the oil bath and placed in the air to cool naturally to room temperature;
[0106] S2.3: The product obtained by the reaction is filtered out and repeatedly washed with DMF solution to dissolve and remove unreacted zinc ions and 1,4-phthalic acid;
[0107] S2.4: Finally, the rinsed sample is immersed in chloroform and dried in a vacuum oven to obtain MOF-5;
[0108] S3: Preparation of casting solution,
[0109] The polyimide P84 powder was dissolved in N, N-dimethylformamide, stirred at 80°C for 36 hours, then MOF-5 was added and stirred at 80°C for 36 hours, and then vacuum degassing was performed for 12 hours to obtain a casting solution, wherein MOF-5 accounted for 10% of the mass of the polyimide P84 powder, and the polyimide P84 powder accounted for 30% of the total mass of the casting solution;
[0110] S4: Preparation of MOF-5 thermally cross-linked modified polyimide film,
[0111] The casting liquid is poured into the liquid storage tank of the rotary spraying machine, and the casting liquid is evenly rotary sprayed onto the α-Al2O3 support. After natural drying, a rotary sprayed film is obtained. The rotary sprayed film is soaked in N, N-dimethylformamide for 6 days, and then vacuum dried at 80°C for 12 hours. The dried rotary sprayed film is then placed in a tubular furnace and calcined at 300°C for 4 hours in a nitrogen atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film. The obtained MOF-5 thermally cross-linked modified polyimide film is stored in a nitrogen atmosphere.
[0112] Comparative Example 1
[0113] Compared with Example 1, the difference of Comparative Example 1 is that, in step S3, the step of adding MOF-5 is removed, and the other steps remain unchanged, and a polyimide film is prepared, which is recorded as Comparative Example 1.
[0114] Comparative Example 2
[0115] Compared with Example 1, the difference of Comparative Example 2 is that, in step S4, the thermal crosslinking operation is removed, and after obtaining the spin-sprayed film, the spin-sprayed film is soaked in N,N-dimethylformamide for 3 days, and then vacuum-dried at 40°C for 8 hours. The remaining steps remain unchanged to prepare a MOF-5 modified polyimide film, which is recorded as Comparative Example 2.
[0116] Gas separation performance test
[0117] The MOF-5 thermally cross-linked modified polyimide films prepared in Examples 1 to 4, the polyimide films prepared in Comparative Example 1, and the MOF-5 modified polyimide films prepared in Comparative Example 2 were respectively packaged in a component, and the performance of each film was tested under the conditions of a pressure value of 1 MPa and a temperature of 25° C. The test gases included CH4, CO2, He, and N2. The test results of each film are shown in Table 1.
[0118] Table 1 Gas separation performance results
[0119]
[0120] It can be seen from the data in Table 1 that the permeability and selectivity of helium and other gases in the polyimide film without MOF-5 modification are not ideal, while the helium flux and selectivity of the polyimide film modified with MOF-5 are greatly improved, and the He / CH4, He / N2 and He / CO2 selectivities can reach 466, 458, and 381, respectively. It can be concluded that the introduction of MOF-5 can greatly improve the transmission efficiency and selectivity of polyimide film for helium, and in the process, it can also collect other types of gases.
[0121] Anti-plasticization performance test
[0122] Using He / CO2 / CH4 ternary mixed gas as feed gas and controlling the feed pressure, the anti-plasticization performance and helium flux change of the MOF-5 thermal cross-linked modified polyimide film prepared in Example 4, the polyimide film prepared in Comparative Example 1, and the MOF-5 modified polyimide film prepared in Comparative Example 2 were tested. The anti-plasticization performance test and helium flux change results of Example 4, Comparative Example 1, and Comparative Example 2 are shown in Figures 1 and 2. Figure 1 , Figure 2 and Figure 3 shown.
[0123] from Figure 1-3 From the anti-plasticization performance test chart, it can be seen that with the continuous increase of the inlet pressure, the separation rate of the polyimide film without MOF-5 and the MOF-5 modified polyimide film without thermal crosslinking and only adding MOF-5 decreases rapidly, indicating that the stability of this type of membrane is very low. The MOF-5 thermally cross-linked modified polyimide film with MOF-5 added and thermally crosslinked has stable gas separation efficiency and excellent anti-plasticization performance, and the maximum helium flux can reach 300GPU.
[0124] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A method for preparing a MOF-5 thermally cross-linked modified polyimide film, characterized in that: The steps include: S1: Preparation of α-Al2O3 support, grinding α-Al2O3 powder and pressing it into sheets, drying, high-temperature firing, grinding, cleaning and drying to obtain α-Al2O3 support, which is dried and stored for later use; S2: Synthesis of MOF-5, Zn(NO3)·6H2O and 1,4-phthalic acid were dissolved in DMF solvent, reacted in an oil bath, and the product obtained by the reaction was filtered, rinsed and dried to obtain MOF-5; S3: Preparation of casting solution: dissolving polyimide in a solvent, then adding MOF-5, heating, stirring, and vacuum degassing to obtain a casting solution; S4: Preparation of MOF-5 thermally cross-linked modified polyimide film, spin-spraying the casting liquid onto an α-Al2O3 support, and obtaining a spin-sprayed film after natural drying, and immersing the spin-sprayed film in a solvent, vacuum drying, and calcining the dried spin-sprayed film under an inert gas atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film, and storing the obtained MOF-5 thermally cross-linked modified polyimide film under an inert gas atmosphere.
2. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 1, characterized in that: step S1: Preparation of α-Al2O3 support, specifically including the following steps: S1.1: Pour α-Al2O3 powder into a mortar, add deionized water and grind vigorously until the powder is uniform; S1.2: Pour the ground α-Al2O3 powder into a film-making mold and press it into a sheet using a film press to obtain a film sheet; S1.3: Place the membrane in a humidity chamber at a temperature of 40-55°C and a humidity of 60-65% to allow the membrane to lose water slowly and not easily break; S1.4: placing the dried membrane into a high temperature furnace and sintering it at 1200-1300°C to form an α-Al2O3 carrier to serve as a support for the membrane; S1.5: Place the fired α-Al2O3 slide on a polishing machine for polishing, then rinse with deionized water, and then soak with alcohol to remove oil stains and dirt on the surface of the α-Al2O3 slide; S1.6: Finally, the soaked α-Al2O3 substrate is placed in an oven for drying to obtain an α-Al2O3 support body, which is then dried and stored for later use.
3. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 2, characterized in that: step S2: Synthesis of MOF-5, specifically comprising the following steps: S2.1: Add the DMF solvent that has been previously dehydrated by a 4A molecular sieve into a round-bottom flask, introduce nitrogen into the round-bottom flask to fully discharge the oxygen dissolved in the DMF solvent, and obtain a pretreated DMF solvent; S2.2: Then, Zn(NO3)·6H2O and 1,4-phthalic acid in a molar ratio of 1:4 are added to the round-bottom flask and gently shaken until they are evenly dissolved. After Zn(NO3)·6H2O and 1,4-phthalic acid are completely dissolved in the pretreated DMF solvent, the liquid in the round-bottom flask is transferred to a glass container, the glass container is sealed with a cover and reacted in a constant temperature oil bath. After the reaction is completed, the glass container is taken out from the oil bath and placed in the air to cool naturally to room temperature; S2.3: The product obtained by the reaction is filtered out and repeatedly washed with DMF solution to dissolve and remove unreacted zinc ions and 1,4-phthalic acid; S2.4: Finally, the rinsed sample is immersed in chloroform and placed in a vacuum oven to dry to obtain MOF-5.
4. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 3, characterized in that: Step S3: Preparation of casting solution, specifically comprising the following steps: Dissolve polyimide in a solvent, stir at 40-80°C for 12-36 hours, then add MOF-5 and stir at 60-80°C for 12-36 hours, then vacuum degassing for 6-12 hours to obtain a casting solution.
5. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 4, characterized in that: MOF-5 accounts for 3-10% of the mass of polyimide, and polyimide accounts for 20-30% of the total mass of the casting solution.
6. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 5, characterized in that: Step S4: Preparation of MOF-5 thermally cross-linked modified polyimide film, specifically comprising the following steps: The casting liquid is poured into the liquid storage tank of the rotary spraying machine, and the casting liquid is evenly rotary sprayed onto the α-Al2O3 support. After natural drying, a rotary sprayed film is obtained. The rotary sprayed film is soaked in a solvent for 3-6 days, and then vacuum dried at 40-80°C for 8-12 hours. Subsequently, the dried rotary sprayed film is placed in a tubular furnace and calcined at 200-300°C for 2-4 hours in an inert gas atmosphere to obtain a MOF-5 thermally cross-linked modified polyimide film. The obtained MOF-5 thermally cross-linked modified polyimide film is stored in an inert gas atmosphere.
7. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 4 or 6, characterized in that: The solvent is any one of nitrogen-methylpyrrolidone and N,N-dimethylformamide.
8. The method for preparing the MOF-5 thermally cross-linked modified polyimide film according to claim 6, characterized in that: The inert gas in step S4 is nitrogen.
9. A MOF-5 thermally cross-linked modified polyimide film, prepared by the method for preparing a MOF-5 thermally cross-linked modified polyimide film according to any one of claims 1 to 8.
10. Use of the MOF-5 thermally cross-linked modified polyimide film according to claim 9 in helium separation.
Citation Information
Patent Citations
Preparation method and application of fluorine-containing crosslinkable polyimide-based carbon molecular sieve membrane
CN115945079A
Carbon molecular sieve membrane as well as preparation method and application thereof
CN116571099A
Cited By
MOF modified hollow polyimide fiber material
CN121130677A